PERANAN GURU TAMAN KANAK-KANAK DALAM MEMBANTU MENGATASI SISWA BERMASALAH - Suri, Dharlinda (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2014)
The need for guidance services in kindergarten emerges from the characteristics and developmental problems that occur in childhood. During the development of kindergarten children, the problem may hinder the achievement of the development of the next period, and also affects other aspects of development. Guidance services as an attempt to aid the teacher in children carried out jointly with the learning processes that occur. This means that when the teachers teach can also act as mentors children. Teachers understanding of the problems experienced by children of kindergarten are different from each other making teachers need to help children overcome problems flexibly. Teachers can not provide assistance with the same approach to each child, because it needs solving problems in children different from each other.